(untitled) (International journal of medical sciences, 2026)
Infectious diseases remain a leading cause of morbidity and mortality among children under five years of age worldwide. Immunization programs have significantly reduced the incidence of vaccine-preventable diseases; however, gaps in vaccination coverage continue to pose public health challenges.This study aims to evaluate the role of vaccination in preventing infectious diseases in early childhood and to analyze its impact on morbidity reduction and overall pediatric health outcomes.A descriptive-analytical review of pediatric clinical records and epidemiological data was conducted. Data regarding vaccination status, incidence of common infectious diseases (measles, pertussis, influenza, pneumococcal infections), hospitalization rates, and complication frequency were analyzed. Comparative assessment was performed between vaccinated and partially or non-vaccinated children aged 0–5 years.Fully vaccinated children demonstrated significantly lower incidence rates of vaccine-preventable infections compared to non-vaccinated groups. Hospitalization rates and severity of complications were markedly reduced among immunized children. In contrast, incomplete immunization was associated with higher susceptibility to outbreaks and increased risk of severe disease progression.Vaccination plays a critical role in reducing the burden of infectious diseases in early childhood. High immunization coverage contributes to decreased morbidity, prevention of complications, and improved public health outcomes. Strengthening immunization programs and public awareness remains essential for sustaining disease prevention efforts.